Some Regulation Mechanisms of Candidate Genes for Human Cardiovascular Diseases - Abdu Esmael; Tesfaye Sisay (Journal of Hypertension and Cardiology, 2021)
Cardiovascular disease is actually a major cause of mortality, illness and hospitalization worldwide. Several risk factors have been identified that are strongly associated with the development of cardiovascular disease. Public prevention strategies have relied predominately on managing environmental factors that contribute to cardiovascular disease, such as obesity, smoking and lack of exercise. The understanding of the role of genetics in cardiovascular disease development has become much more important to link genetics with the onset of disease and response to therapy. This seeks to examine how genes can predispose individuals to cardiovascular disease and how this knowledge might be applied to more comprehensive preventive strategies in the future. In addition, the review explores possibilities for genetics in cardiovascular disease treatment, particularly through the use of identified driver genes and gene therapy. To fully understand the biological implications of these associations, there is a need to relate them to the exquisite, multilayered regulation of protein expression and regulatory elements, mutation, microRNAs and epigenetics. Understanding how the information contained in the DNA relates to the operation of these regulatory layers will allow us not only to better predict the development of cardiovascular disease but also to develop more effective therapies.
Keywords: Cardiovascular disease